RISADA PEGA: A Mnemonic Method in Portuguese for Alarm Criteria in Emergency Headaches - Silva Júnior, Hilton Mariano da; Cardoso, Larissa Volpini (Headache Medicine, 2021)
Introduction We present the first mnemonic method in Portuguese, “RISADA PEGA”, for alarm criteria in emergency headaches in order to facilitate their identification and diagnosis. A search was made through different databases for a mnemonic method regarding alarm criteria in emergency headaches, and methods in English and Spanish were found, but there was no mention of one written in Portuguese. Result With that in mind, the method “RISADA PEGA” (“laughter spreads”, in English) was created: Repentina / (Sudden) I - Início depois dos 50 anos / (onset in a patient older than 50) S - Sinais e/ou sintomas de doenças sistêmicas ou neurológicas / (Signs and/or symptoms of systemic or neurologic diseases) A - Anormalidades no exame neurológico/(abnormalities upon neurologic examination) D - Depressão da imunidade(AIDS, Câncer)/Depressed immunity (HIV or cancer) A - Antecedentes: doenças que podem acometer o SNC; número de vindas ao PShistória familiar de cefaleia)/(Prior conditions: diseases affecting the central nervous system; number of visits to the health center, history of headache in the family) P - Padrão alterado (mudança no padrão anterior da cefaleia)/(change in headache pattern) E - Esforço/exertion) G - Gravidez/(pregnancy) A - Autonomia (sinais autonômicos)/(autonomic signs) Conclusion In the emergency department, an acute headache is a symptom presented by 2%-4% of admitted patients. Secondary headaches are associated with high morbidity and mortality. A need exists for the quick identification of the alarm criteria and a correct stratification of the patient’s risk, proper diagnosis and treatment. There are also time constraints in the emergency department. This shows the usefulness of a method for quick identification of the alarm criteria. We believe this is a useful tool for medical education and a clinical aid for clinical practitioners, it may also be a way to educate patients regarding the alarm criteria for emergency headaches.